PENGARUH PENAMBAHAN TEPUNG KEDELAI KUNING SEBAGAI FAT REPLACER DALAM PEMBUATAN SPONGE CAKE [THE EFFECT OF ADDING YELLOW SOYBEAN FLOUR AS A FAT REPLACER IN THE PRODUCTION OF SPONGE CAKE] - Ratna Handayani (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2022)
Sponge cake is a cake that requires eggs as the main raw material in the formation of foam, coagulation, and emulsification. Vegetable protein is widely used to replace the use of eggs or to replace some of the eggs in some baking products. One source of vegetable protein that has the potential to replace the role of eggs in making sponge cake is yellow soybean flour. The use of other additives such as emulsifiers is needed to improve the quality of the final sponge cake product. The purpose of this study was to determine the potential of roasted full-fat soy flour (FFSF) to replace eggs in making sponge cake with the addition of a soy lecithin emulsifier. In this study, substitution ratios of roasted FFSF and eggs were used (0:100, 25:75, 50:50, 75:25, 100:0) and variations in the concentration of soy lecithin (0, 2, 4, 6%) to determine the effect of physical characteristics of the resulting sponge cake. The addition of roasted FFSF as a substitute for eggs reduces the physical characteristics of sponge cake in terms of dough density and stability, height, volume, and specific volume of cake, color, cake texture, but reduces the value of moisture loss from the cake. The addition of soy lecithin can improve the quality of the dough and the resulting final product. Sponge cake with the best formulation that did not differ from the control was sponge cake with a substitution ratio of roasted FFSF and egg 25:75 and a soy lecithin concentration of 2%.Bahasa Indonesia Abstract:Sponge cake merupakan kue yang membutuhkan telur sebagai bahan baku utama dalam pembentukan buih, koagulasi dan emulsifikasi. Beberapa tanaman banyak dimanfaatkan sebagai sumber protein nabati yang dimanfaatkan untuk menggantikan sebagian telur. Protein nabati banyak dimanfaatkan untuk menggantikan penggunaan telur atau menggantikan sebagian jumlah telur pada beberapa produk baking. Salah satu sumber protein nabati yang berpotensi untuk menggantikan peranan telur dalam pembuatan sponge cake adalah tepung kedelai kuning. Penggunaan bahan tambahan lain seperti emulsifier diperlukan untuk meningkatkan kualitas produk akhir sponge cake. Tujuan dari penelitian ini adalah untuk menentukan jumlah tepung kedelai roasted full-fat soy flour (FFSF) untuk menggantikan telur dalam pembuatan sponge cake dengan penambahan emulsifier lesitin kedelai. Pada penelitian ini digunakan rasio substitusi roasted FFSF dan telur (0:100, 25:75, 50:50, 75:25, 100:0) dan variasi konsentrasi lesitin kedelai (0, 2, 4, 6%) untuk menentukan pengaruh juga karakteristik fisik sponge cake yang dihasilkan. Penambahan roasted FFSF sebagai pengganti telur menurunkan karakteristik fisik sponge cake dari segi densitas dan stabilitas adonan, tinggi, volume, dan volume spesifik cake, warna, tekstur cake, namun menurunkan nilai moisture loss pada cake. Penambahan lesitin kedelai dapat memperbaiki kualitas adonan dan produk akhir yang dihasilkan. Sponge cake dengan formulasi terbaik adalah sponge cake dengan rasio substitusi roasted FFSF dan telur 25:75 dan konsentrasi lesitin kedelai 2%.